Auditing in the Era of Cybersecurity: Challenges and Solutions - Apriyanto, Apriyanto; Mudawanah, Siti; Sutanto, Edi; Purnomo, Adi Dwi; Murniawan, Muhammad Wahid (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
As threats and risks increase in the digital world, auditing in the cyber security era faces significant new challenges. Rapid digital change has increased the complexity of information systems, which makes the audit environment more complicated and requires new approaches to assessing the effectiveness of security controls. The increase in cyber threats that can threaten the integrity, confidentiality and availability of data is one of the main challenges facing auditors. Increasingly varied and sophisticated cyberattacks require proactive and adaptive audit techniques. Auditors must have the ability to evaluate cyber threats and evaluate how they impact a company's information systems and internal controls. Additionally, rapid technological advances such as cloud computing, artificial intelligence, and the Internet of Things (IoT) make auditing more difficult. To overcome this problem, risk and technology-based audits must be implemented. Lastly, training and development of auditors' skills is essential to address this issue. Auditors must keep their skills updated on cybersecurity and the latest technologies. Lastly, training and development of auditors' skills is essential to address this issue. Auditors must keep their skills updated on cybersecurity and the latest technologies. Investment in ongoing training and certification of cybersecurity specialists will help them discover and address risks more effectively, and ensure more comprehensive and useful audits in an increasingly complex environment.